Assessment of resilience in rural areas: The case of Bağlıköy, Cyprus - Mümüne Selen Abbasoğlu; Fatma Bıldır (Journal of Design for Resilience in Architecture and Planning)
Recent developments have significantly impacted both urban and rural areas, leading to increased migration from rural to urban regions and considerable challenges in rural areas. Rural activities have decreased due to the reduction in population and the labour force, affecting economic, environmental, social, and demographic structures. These natural and artificial changes constitute potential threats to rural resilience. Consequently, rural resilience analysis has become essential to ensuring the sustainability and well-being of rural communities in the face of economic, environmental, and social challenges. Rural resilience is defined as the ability to adjust, transform and cope with change in response to ever-changing regional dynamics. There are four key components of rural resilience: economic resilience, social resilience, environmental resilience, and cultural resilience. Robust infrastructure, including transportation, communication, and healthcare systems, maintains connectivity and access to essential services during adverse events. The research focuses on the cultural, economic, environmental, and social factors influencing the resilience of rural area. Besides, this study hypothesizes that the resilience of rural areas is significantly influenced by vulnerabilities resulting from regional transformations, and both natural and artificial impacts. Bağlıköy village was selected as the case study area to examine this hypothesis. A SWOT analysis of Bağlıköy’s rural resilience helps identify internal strengths and weaknesses, as well as external opportunities and threats that influence its ability to withstand and recover from challenges. The assessment of the vulnerability of rural areas to natural and artificial effects experienced with regional transformations linked to resilience factors. In conclusion, the study evaluates the rural area's resilience and provides recommendations to enhance its sustainability and adaptive capacity.